2014
DOI: 10.1016/j.jvs.2013.10.069
|View full text |Cite
|
Sign up to set email alerts
|

Creation of an iliac arteriovenous shunt lowers blood pressure in chronic obstructive pulmonary disease patients with hypertension

Abstract: Percutaneous iliac arteriovenous fistula creation for COPD causes a significant and persistent lowering of blood pressure in patients with co-existing hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 14 publications
1
37
0
2
Order By: Relevance
“…Compared with baseline (145±12/86±13 mm Hg), systolic and diastolic BP were significantly reduced after 6 (130±18/71±13 mm Hg, P<0.01) and 12 months (132±18/67±13 mm Hg, P<0.01), respectively. 181 No clinical meaningful BP reduction was seen in normotensive COPD patients after creation of an AVF using the ROX coupler.…”
Section: Arteriovenous Fistulamentioning
confidence: 98%
See 1 more Smart Citation
“…Compared with baseline (145±12/86±13 mm Hg), systolic and diastolic BP were significantly reduced after 6 (130±18/71±13 mm Hg, P<0.01) and 12 months (132±18/67±13 mm Hg, P<0.01), respectively. 181 No clinical meaningful BP reduction was seen in normotensive COPD patients after creation of an AVF using the ROX coupler.…”
Section: Arteriovenous Fistulamentioning
confidence: 98%
“…Detailed technical information about deployment of the device is given elsewhere. 181 Several mechanisms are hypothesized to cause BP reduction after creation of an AVF. 182 Reduction in total systemic vascular resistance, despite an increment in cardiac output, is considered to be the key mechanism.…”
Section: Arteriovenous Fistulamentioning
confidence: 99%
“…66 A subsequent open label study of 24 patients with COPD and mild hypertension demonstrated a significant reduction in office BP from 145/86 to 132/67 mmHg at 12 months leading to a repurposing of the device for the hypertension indication. 67 …”
Section: Central Iliac Arteriovenous Anastomosismentioning
confidence: 99%
“…Begleitend zeigte sich in den retrospektiven Analysen ein Blutdruckabfall[25].DerHauptmechanismus der Blutdrucksenkung ist die Reduktion des peripheren vaskulären Widerstandes. Die Reduktion des peripheren vaskulären Widerstands und das verminderte effektive arterielle Volumen verbessern die vaskuläre Compliance, was wiederum die reflektierten Pulswellen vermindert und somit zu einer verminderten Herzarbeit führt.…”
unclassified